Supportive work environment effect on employee retention at Bit Group Sdn Bhd / Nor Adibah Zailan - Zailan, Nor Adibah (Faculty of Business and Management, 2019)
This paper examines on employee retention and the relationship with organizational support, supervisory support and job satisfaction. Employee retention has become a major concern among organization nowadays. This is because there is increasing number of employee turnover especially in IT sector. Therefore, creating a supportive work environment is one of the efforts in order to retain the employees in the organization. This study highlighted and defines the basic concept of organizational support, supervisory support, job satisfaction and employee retention. The total population for this study consist 257 employees. The questionnaire has been distributed to 257 respondents and 183 valid questionnaire were returned. The data collected was processed using Statistical Package for Social Science version 20. The data had been analysed using Descriptive, Pearson Correlation and Multiple Regressions analyses. The results from this study revealed that there is a positive and significant relationship between two independent variable and dependent variable which is between supervisory support, job satisfaction and employee retention. However, there is no significant relationship between organizational support and employee retention. Therefore, the results indicates there are many other factors that can contribute to employee retention which are not included in this research.